A GEOCHEMICALLY CONSISTENT HYPOTHESIS FOR MORB GENERATION - Lundstrom C.C.; Gill J.; Williams Q. (My University, 1999)
Geochemical observations of MORB including U-series disequilibria are used to examine the processes and timescales of MORB melt generation. Incompatible elements in MORB suggest that the MORB source region consists of a depleted lherzolite matrix interspersed with chemically enriched mafic veins. Wide variations in Th/U distinguish these source variations in MORB better than / and document that the relative chemical homogeneity of normal MORB reflects efficient melt mixing rather than a homogeneous source. Spinel compositional variations in MORB and in mantle solids (abyssal peridotites and dunites) reflect reactive flow of melts having significant compositional variations. High Cr# spinels result from reactive flow of chemically enriched melts derived from the mafic vein source ascending through the lherzolite of the upper melting column. High Cr# and TiO2 contents in dunite spinels indicate that dunites form by reactive flow of enriched melts through the upper melting column. Once formed, dunites act as high permeability pathways for melt from surrounding lherzolite and are responsible for the “fractional signatures” observed in the major element chemistry, melt inclusions, abyssal peridotites and Lu–Hf systematics of MORB. Based on the recognition that there are two sources melting beneath ridges that have different porosity characteristics, a melting model consistent with evidence for both fractional and equilibrium porous flow melting is proposed. In this model, the presence of dunite channels affect melt generation and transport in the lherzolite matrix, suggesting that mantle heterogeneity may be critical to the physical aspects of melting and melt transport in the mantle beneath mid-ocean ridges. U-series disequilibria provide information on how melting occurs in the two endmember sources and suggest that melt porosities in the lherzolite may be as low as 0.1%. Melt within lherzolite maintains equilibrium with the coexisting solid while it ascends porously. Primitive MORB with high Mg# consistently have low excesses or deficits with major element chemical signatures of equilibration near 1.0 GPa suggesting that the depleted endmember melt maintains chemical equilibrium with lherzolite until shallow mantle depths (∼30 km). Melt porosities in enriched heterogeneities remain below 1% for perhaps 10s of km before losing chemical equilibrium with the solid during transport in the upper melting column. Because the porosities required by the observed disequilibria are small, the transition to porosities large enough to form “veins” of melt must occur over a timescale which is very long in comparison to the half-life and significantly long for . Thus, instantaneous transport dynamic melting models appear incompatible with the observed disequilibria even when initial melt productivities as low as 0.05%/km are used.